Exosomes Derived from Bone Mesenchymal Stem Cells Alleviate Compression-Induced Nucleus Pulposus Cell Apoptosis by Inhibiting Oxidative Stress. (25th October 2021) - Hu, Yiqiang; Tao, Ranyang; Wang, Linfang; Chen, Lang; Lin, Ze; Panayi, Adriana C.; Xue, Hang; Li, Hui; Xiong, Liming; Liu, Guohui
Abstract : Oxidative stress is relevant in compression-induced nucleus pulposus (NP) cell apoptosis and intervertebral disc (IVD) degeneration. Exosomes derived from bone mesenchymal stem cells (BMSCs-Exos) are key secretory products of MSCs, with important roles in tissue regeneration. This research is aimed at studying the protective impact of BMSCs-Exos on NP cell apoptosis caused by compression and investigating the underlying mechanisms. Our results indicated that we isolated BMSCs successfully. Exosomes were isolated from the BMSCs and found to alleviate the inhibitory effect that compression has on proliferation and viability in NP cells, decreasing the toxic effects of compression-induced NP cells. AnnexinV/PI double staining and TUNEL assays indicated that the BMSCs-Exos reduced compression-induced apoptosis. In addition, our research found that BMSCs-Exos suppressed compression-mediated NP oxidative stress by detecting the ROS and malondialdehyde level. Furthermore, BMSCs-Exos increased the mitochondrial membrane potential and alleviated compression-induced mitochondrial damage. These results indicate that BMSCs-Exos alleviate compression-mediated NP apoptosis by suppressing oxidative stress, which may provide a promising cell-free therapy for treating IVD degeneration.